2021
DOI: 10.1101/2021.07.06.21260040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid vigilance and episodic memory decrements in COVID-19 survivors

Abstract: Recent studies indicate that COVID-19 infection can lead to serious neurological consequences in a small percentage of individuals. However, in the months following acute illness, many more suffer from fatigue, low motivation, disturbed mood, poor sleep and cognitive symptoms, colloquially referred to as ‘brain fog’. But what about individuals who do not report any ongoing symptoms after recovering from COVID-19? Here we examined a wide range of cognitive functions critical for daily life (including sustained … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…The observed correlation with a marker of acute inflammation may reflect a causal relationship beyond the severity of respiratory problems; however, given the high correlation to other clinical features of the acute phase, work seeking to disentangle underlying clinical causes of the observed cognitive deficits will require either substantial sized cohorts with sufficient power to delineate highly correlated predictors or additional data types, such as brain imaging in order to detect associations with markers in specific types of neuropathology. Some previous studies have observed significant recovery across time in terms of cognitive symptoms 18 and imaging measures of brain function. 33 In accordance with these studies, we did observe slow and nonsignificant trends towards reduced deficits in both accuracy and response latency as a function of time from illness.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The observed correlation with a marker of acute inflammation may reflect a causal relationship beyond the severity of respiratory problems; however, given the high correlation to other clinical features of the acute phase, work seeking to disentangle underlying clinical causes of the observed cognitive deficits will require either substantial sized cohorts with sufficient power to delineate highly correlated predictors or additional data types, such as brain imaging in order to detect associations with markers in specific types of neuropathology. Some previous studies have observed significant recovery across time in terms of cognitive symptoms 18 and imaging measures of brain function. 33 In accordance with these studies, we did observe slow and nonsignificant trends towards reduced deficits in both accuracy and response latency as a function of time from illness.…”
Section: Discussionmentioning
confidence: 86%
“…There was statistical power of 95% to detect medium strength correlations of r = 0.50 at two tailed alpha p < 0.05. Participants completed a custom computerised cognitive assessment battery under supervised conditions via the Cognitron platform, 17,18 comprising 8 tasks deployed on an iPad (Supplemental Methods), as well as standard mood, anxiety and post-traumatic stress scales, specifically, the Generalized Anxiety Disorder 7 (GAD-7), 19 the Patient Health Questionnaire 9 (PHQ-9) 20,21 and the PTSD Checklist for Diagnostic and Statistical Manual of Mental Disorders 5 (PCL-5) 22 in a return visit to the hospital on average 179 days after illness onset (SD=62 interquartile range=81).…”
Section: Data Collectionmentioning
confidence: 99%
“…Due to the cross-sectional design of our present work, we cannot demonstrate longitudinal development of DMI-parameters. However, few studies (including a follow-up investigation of patients from our cohort 3 ) provide longitudinal data on cerebral glucose metabolism assessed by 18 F-FDG PET and cognitive impairments, 30 , 46 , 47 both being significantly associated with V-CSF in our cross-sectional data. Here, cortical dysfunction and cognitive deficits were grossly reversible, albeit minor residuals may still be present six months after COVID-19.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the larger burden of comorbidities in COVID-19 patients could be seen as a source of confound. The substantial reversibility of cortical dysfunction and cognitive deficits, 30 , 46 , 47 factors tightly coupled to V-CSF increase, however argue against a major impact of such static factors. Lastly, as we did not include respective control groups (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 A third aspect is that neurocognitive impairment has not only frequently been self-reported after acute SARS-CoV-2 infection as in this study, but has already been validated in several studies as measurable deficiencies in reasoning, problem solving, spatial planning, target detection and diverse memory functions. [27][28][29][30][31][32] At least some of the studies did not suggest improvement of cognitive performance measures after COVID-19 over time, 23,28 and we also had no evidence of decreasing neurocognitive symptom prevalence within our observation period six to 12 months after acute infection. This may indicate that, similar to fatigue, this disorder might develop into a chronic health problem in an unknown proportion of patients.…”
Section: Discussionmentioning
confidence: 53%